An experimental study on the evolution of beach profiles under different beach nourishment methods - Meng, Ye; Qu, Zhipeng; Li, Xueyan; Zhu, Meixi; Liang, Bingchen (Frontiers in Marine Science, 2024)
Due to the influence of storm surges, hard coastal protection structures may exacerbate beach erosion, hence beach nourishment methods are considered in coastal protection and restoration efforts. An experiment is conducted in a wave flume to compare the advantages and disadvantages of three types of beach nourishment methods (berm nourishment, profile nourishment, and bar nourishment) under non-storm and storm wave conditions. The experiment analyzes wave height distribution, beach morphology changes, net sediment transport, shoreline recession, beach width increase, and beach volume changes. The findings indicate that the implementation of bar nourishment strategies facilitates the pre-breaking of storm waves, thereby mitigating the disruption caused by wave breaking on water flow dynamics. Moreover, the application of berm and profile nourishment methods proves to be highly effective in expanding the width of the beach and bolstering its stability. However, it is worth noting that bar nourishment exhibits limited efficacy in terms of restoring beach berms and mitigating coastal erosion within the same duration of wave action. The study presents two equations incorporating hydrodynamic parameters to predict the erosion or accretion status of beaches, and compares the predicted results with experimental data, thereby refining the criteria and making the formulas more applicable to beach nourishment projects. These findings provide valuable insights into the strengths and weaknesses of different beach nourishment methods, which will contribute to the implementation of nourishment projects.